Tinjauan Yuridis Peran Penyuluh Agama Islam dalam Pencatatan Nikah di KUA - Mochammad Arifin; Slamet Slamet; M. Abdul Hakim (Universitas Nahdlatul Ulama Blitar, 2026)
Marriage registration is not merely an administrative procedure but a legal instrument that determines the formal validity of a marriage and serves as the foundation for protecting the civil rights of spouses and children within the national legal system. Legal issues arise when the limited number of Marriage Registrars (Pegawai Pencatat Nikah/PPN) at the Office of Religious Affairs (KUA) leads to the involvement of Islamic Religious Counselors in the marriage registration process, even though the normative authority to register marriages is formally vested in the PPN. This study aims to analyze the legal standing of Islamic Religious Counselors in the KUA of Kanigoro District and to examine whether the authority exercised is attributive, delegative, or merely administrative in nature. The research employs a qualitative case study combined with a normative-empirical juridical approach. Data were collected through interviews, observations, and document analysis, and interpreted using statutory and conceptual approaches. The findings indicate that the involvement of Islamic Religious Counselors is administrative-assistive and lacks an explicit attributive or delegative legal basis under Law No. 1 of 1974 and Minister of Religious Affairs Regulation No. 20 of 2019, underscoring the need for clearer regulatory mechanisms to prevent administrative defects affecting legal validity.